Professionalised ’civil society’ vs. grassroots ’uncivil society’? The ’Little Czech’ 20 years later - Slacálek, Ondřej; Svobodová, Eva (Socio.hu Társadalomtudományi Szemle, 2017)
The article is an analysis of the five most distinctive public mobilisations in the Czech Republic in the past 20 years. The analysis builds on two key debates regarding post–communist civil society (civil vs. uncivil society and transactional vs. participatory activism) and also on an analysis of Czech nationalism by the anthropologist Ladislav Holý. In the empirical part, it looks at the image of the nation and civil society in the cases of the movement against the opposition agreement (Thank You, Now Go, and Czech Television – A Public Affair), the movement against the American radar base, the anti–austerity protest movement, the anti–Roma protests and the islamophobic movement. The self–conception of the movements is complemented by an analysis of the images of them that were held by their opponents. The article points to the vague and indefinite nature of Czech national identity, and the fact that in the past two decades, it has been markedly connected with the image of the West and a relatively low significance of class. It also shows that “NGO–ised” transactional activism has become the subject of hostile rhetoric which may rely on the legitimacy deficit that this type of activism has. However, it concludes that to a certain extent, it shares this type of deficit with another type of civic activism; in the case of participatory activism, it identifies a dilemma between the polarisation of society and political ineffectiveness. Keywords: Ladislav Holý, uncivil society, transactional activism, Czech Islamophobia, social movements